Constructing Built‐in Electric Field in Heterogeneous Nanowire Arrays for Efficient Overall Water Electrolysis - Zhang, Shucong; Tan, Chunhui; Yan, Ruipeng; Zou, Xifei; Hu, Fei‐Long; Mi, Yan; Yan, Cheng; Zhao, Shenlong (Angewandte Chemie International Edition, 2023)
Efficient bifunctional electrocatalysts for hydrogen and oxygen evolution reactions are key to water electrolysis. Herein, we report a built‐in electric field (BEF) strategy to fabricate heterogeneous nickel phosphide‐cobalt nanowire arrays grown on carbon fiber paper (Ni2P‐CoCH/CFP) with large work function difference (ΔΦ) as bifunctional electrocatalysts for overall water splitting. Impressively, Ni2P‐CoCH/CFP exhibits a remarkable catalytic activity for hydrogen and oxygen evolution reactions to obtain 10 mA cm−2, respectively. Moreover, the assembled lab‐scale electrolyzer driven by an AAA battery delivers excellent stability after 50 h electrocatalysis with a 100 % faradic efficiency. Computational calculations combining with experiments reveal the interface‐induced electric field effect facilitates asymmetrical charge distributions, thereby regulating the adsorption/desorption of the intermediates during reactions. This work offers an avenue to rationally design high‐performance heterogeneous electrocatalysts. By proposing and fabricating Ni2P‐CoCH heterostructure with large ΔΦ as a model catalyst for overall alkaline water electrolysis, the introduction of a strong built‐in electric field (BEF) is successfully realized to create the asymmetrical charge distributions on catalyst surfaces. The negative charge‐enriched Ni2P and positive charge‐enriched CoCH as active sites separately achieve high hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) activities.